The Effect of Blockbusters Game and Gender on Grade Ten Students’ Listening Comprehension of SMAN 1 Melaya in the Academic Year 2010/2011. Thesis, Program Studi Pendidikan Bahasa Program Pascasarjana UniversitasPendidikan Ganesha Singaraja. - Aditya Septirino, I Komang (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
ABSTRACT Septirino, I Komang Aditya (2012). The Effect of Blockbusters Game and Gender on Grade Ten Students? Listening Comprehension of SMAN 1 Melaya in the Academic Year 2010/2011. Thesis, Program Studi Pendidikan Bahasa Program Pascasarjana UniversitasPendidikan Ganesha Singaraja.Keywords:blockbusters game,gender,listening comprehensionThe main objective of this study was to investigate whether there was a significant difference in listeningcomprehension amongmale and female students who were treated differently by using Blockbusters game and conventional technique. The subjects of the study were 4 classes of grade ten students of SMAN 1 Melaya determined by using random sampling. The study involved 6 sessions of treatments and a post test at the end of the treatment. This study used ?The Posttest Only Control Group Design? as the research design. The gathered data were analyzed by usingdescriptiveand inferential statistics. The result of the data analysis showed that: (1) there was significant difference in listening comprehension between the students who were taught by using Blockbusters game and those who were treated with the conventional technique, (2) there was significant difference of students? listening comprehension between female and male students, (3) There was no interaction between the teaching techniquesappliedand gender difference. Based on the finding above, it is recommended for English teacher to consider Blockbusters game as an alternative listening technique applied in teaching listening inorder to optimize students?listeningcomprehension.2ABSTRAKSeptirino, I Komang Aditya (2012). Efek dari Permainan Blockbusters dan Gender terhadap Kemampuan Mendengarkan Murid Kelas X di SMAN 1 Melaya pada Tahun Ajaran 2010/2011. Tesis, Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Pendidikan Ganesha Singaraja. Kata kunci: blockbusters game, gender,kemampuanmendengarkan. Penelitian ini bertujuan untuk mendeskripsikan perbedaan kemampuan mendengarkan antara murid perempuan dan laki-laki yang dikelola berbeda dengan menggunakan permainan Blockbusters dan teknik mendengarkan konvensional. Subyek dari penelitian ini adalah 4 kelas dari 8 kelas X di SMAN 1 Melaya yang diperoleh secara random. Penelitian ini menggunakan desain ?The Posttest Only Control Group Design?. Data yang diperoleh dianalisis dengan menggunakan statistik deskriptif dan inferensial. Temuan penelitian menunjukkan, bahwa: (1) terdapat perbedaan kemampuan mendengarkan yang signifikan antara murid yang diajar dengan permainan Blockbuster dan teknik konvensional, (2) terdapat perbedaan kemampuan mendengarkan antara murid perempuan dan laki-laki, (3) tidak terdapatinteraksi antara teknik mengajar dan perbedaan gender. Berdasarkantemuan penelitian, disarankan untuk menggunakan permainan Blockbusters sebagai salah satu teknik alternatif untuk mengoptimalkan kemampuanmendengarkan siswa.